Efektivitas Metode Role-playing dalam Meningkatkan Pemahaman Materi Khalifah Umar Bin Khattab Pada Pelajaran Pendidikan Agama Islam - Teguh Triyanto, Iwan; Bisri, Moh. (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2024)
This study aims to evaluate the application of the Role-playing method in learning material of Khalifa Umar bin Khattab in PAI subjects at SMP Negeri 2 Mondokan for the 2023/2024 academic year. The subjects of the study included PAI teachers and grade VII students. The results showed that the use of the Role-playing method is effective in improving student learning outcomes. Cognitively, there was a significant increase from pre-cycle with an average value of 58.00 and a success percentage of 58.00%, as well as classical completeness of 40.00%, to cycle I with an average value of 69.33, a success percentage of 69.33%, and classical completeness of 66.67%, and cycle II with an average value of 76.22, a success percentage of 76.22%, and classical completeness of 93.33%. The affective aspect also increased from pre-cycle 50.00% to cycle II 80.55%, while the psychomotor aspect showed an increase from pre-cycle 52.00% to cycle II 82.92%. Learning outcomes on affective and psychomotor aspects have also met or exceeded KKM 65.